Present scenario of laryngeal tuberculosis - Saldanha, Marina; Sima, Natashya H.; Bhat, Vadisha S.; Kamath, Shrinath D.; Aroor, Rajeshwari (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: The objectives of the study were to document the presentation of laryngeal tuberculosis, response to anti-tubercular treatment and objective evaluation of larynx during and post anti-tubercular treatment. Methods: A before and after treatment study including 15 subjects with laryngeal tuberculosis treated in our tertiary health care centre during a three year study period. Clinical presentation, management, subjective self-assessment of voice and objective assessment of larynx by videostroboscopy at the beginning, at two months and at six months of anti-tubercular treatment were documented. Results: Two patients had primary laryngeal tuberculosis and thirteen patients had laryngeal tuberculosis associated with pulmonary tuberculosis. Only one patient was immuno-compromised. Most common presenting symptom was hoarseness (93%). Ulcerative lesions were the most common clinical finding (87%) with the vocal cords being the commonest site involved (80%). All patients responded well to anti-tubercular treatment. Videostroboscopy showed an improvement in vocal cord lesions during treatment. Subjective assessment of voice after two months of anti-tubercular treatment showed marked improvement in voice. At completion of treatment, voice was better but all patients had complaints of residual hoarseness. Conclusions: Primary laryngeal tuberculosis is less common in comparison to laryngeal tuberculosis secondary to pulmonary tuberculosis. With early diagnosis, the response to treatment is satisfactory. Videostroboscopy can be used as an effective tool in monitoring vocal cord changes during the follow- up period.